Use of 5-azacitidine for therapy-related myeloid neoplasms in patients with concomitant active neoplastic disease. (April 2017) - Annereau, M.; Willekens, C.; El Halabi, L.; Chahine, C.; Saada, V.; Auger, N.; Danu, A.; Bermudez, E.; Lazarovici, J.; Ghez, D.; Leary, A.; Pistilli, B.; et al.
Highlights: 30% of patients with t-MDS/AML have a concomitant active neoplastic disorder (CAND). 5-Azacytidine (AZA) treatment is feasible for t-MDS/AML patients with CAND. Active neoplastic treatment in association with AZA is feasible. Response rate and OS are similar between t-MDS/AML with or without CAND. OS of these patients is 12.7 months compared to 0.62 months for untreated patients. Abstract: Background: Patients diagnosed with therapy-related myeloid neoplasms (TRMN) with concomitant active neoplastic disorder (CAND) are usually proposed for best supportive care (BSC). We evaluated the feasibility of using 5-azacytidine (AZA) in this setting. Methods: All patients referred to Gustave Roussy between 2010 and 2015 for TRMN diagnosis (less than 30% blast) and eligible for AZA treatment were included. Patients with CAND proposed for BSC were also described. Patient's outcomes were analyzed based on the presence or not of a CAND. Results: Fifty-two patients with TRMN were analyzed, including 19 patients with CAND (14 eligible for AZA) and 33 without CAND eligible for AZA. The 5 patients with CAND ineligible for AZA had a worst performance status (p = 0.016) at diagnosis and a shorter overall survival (OS) (0.62 months). Baseline characteristics of patients eligible for AZA were similar in the 2 groups except a trend for best performance status in patients with CAND (p = 0.06). Overall response rate (71.4% vs 60.3%), transfusion independence (50.0% vs 45.5%) and OS (12.7 months vs 10.8 months) were similar between patients with and without CAND respectively (p = ns). Conclusion: Here we report the feasibility and efficacy of AZA for selected patients with TRMN and a CAND.